New Techniques in Foot and Ankle Surgery - Thermann, Hajo (Springer International Publishing : Imprint: Springer, 2017)
This book presents in exquisite detail numerous new surgical techniques for the treatment of foot and ankle conditions, as well as the latest refinements of established procedures. All operations are depicted step by step with the aid of superb illustrations, with precise and succinct accompanying descriptions. The author is an expert in the field, with many years of experience, whose goals here are to facilitate the smooth translation of theory into practice and to stimulate further discussions and communications regarding optimal surgical management. The book is already in its second edition in German. Among the key features of this first English edition are the latest advances in arthroscopy, surgical procedures on the Achilles tendon, interventions for treatment of lateral ligament and syndesmotic ankle injuries, surgical interventions on the metatarsophalangeal joint, surgical correction of hindfoot deformities, forefoot surgery, and ankle arthroplasty. The book will be of value for foot and ankle surgeons at all levels.
Keywords: Medicine.; Orthopedics.; Traumatology.; elektronické knihy; electronic books